Development of machine learning enhanced low-cost spectrophotometer for pesticide prediction - Murathathunyaluk, S.; Jinorose, M.; Janpetch, K.; Chanthapanya, N.; Sombatsri, W.; Wongsricha, A.; Chawuthai, R.; Mansouri, S. S.; Anantpinijwatna, A. (My University, 2025)
Conventional analytical methods for measuring pesticide concentrations, such as chromatography, offer high accuracy but require expensive instrumentation, prompting the investigation of cost-effective alternatives like smartphone-based spectrophotometers. Despite their potential, these methods face challenges related to assembly and precision, often requiring human intervention to select appropriate images for analysis. This study presents a novel, affordable spectrophotometer designed for integration with machine learning algorithms. The device captures images of two spectral bands and employs a six-step image processing methodology to prepare images for analysis. A machine learning model trained on four algorithms with feature selection and cross-validation demonstrates high accuracy in predicting chemical concentrations of coloured solutions. The approach achieves 98.5 % accuracy for KMnO4 and 96.7 % for Carbosulfan solutions, comparable to high-end spectrophotometry devices. The design eliminates the need for human intervention, reducing biased selection and result manipulation. However, concentration estimation of non-coloured compounds remains inaccurate, indicating areas for further refinement.
Keywords: Carbosulfan; Cross-Validation; Image Processing; Machine Learning; Spectrophotometer